Problem-Solving Ability in Learning Islamic Education Philosophy Course through IDEAL Stages - Amrullah, Amrullah; Fauziah, Meli; Jamaluddin, Aini Syahira; Bustomi, Ahmad (IJECA (International Journal of Education and Curriculum Application), 2023)
Islamic education philosophy course cultivates students’ critical thinking skill when they are able to solve problems in learning well. Due to the complexity of the course, students often face some difficulties. The aim of this study is to describe problem-solving ability in learning Islamic Education Philosophy course through IDEAL stages (Identify, Define, Examine, Act, and Look). This study used a quantitative method with a descriptive approach. The data were analysed descriptively using manual mathematic calculation. The results of this study revealed that the IDEAL stages were effectively used for solving problems encountered in learning Islamic Education Philosophy course. From the skill test, 8 students got a score of 100 on the A scale with a percentage of 22% who were able to answer correctly and completely in each IDEAL stage. Besides, there were also 10 students who got a score of 97 on A scale with a percentage of 28% who almost carried out all stages correctly and completely. In addition, there were 7 students who got a score of 94 on the B scale with a percentage of 18% which means incomplete in several stages and there were 14 students who got a score of 91 on the B scale with a percentage of 40% which was still weak in several IDEAL stages.